Life‐Sustaining Treatment Documentation in VA Home Based Primary Care Improves With Feedback Reports and Facilitation. - Levy, Cari R.; Magid, Kate H.; Kononowech, Jennifer; Langner, Paula; Sales, Anne (Journal of the American Geriatrics Society, 2026)
Background: The Veterans Health Administration (VHA) Life‐Sustaining Treatment Decisions Initiative (LSTDI) aims to improve documentation of patient preferences for life‐sustaining treatment (LST), particularly in high‐risk populations such as those served by Home Based Primary Care (HBPC) programs. Despite this mandate, LST documentation in HBPC remains variable. Previous studies suggest audit and feedback may be insufficient when used alone. This study evaluated whether combining audit and feedback with tailored implementation facilitation can increase and sustain LST documentation rates in HBPC. Methods: We evaluated the prospective implementation of a longitudinal intervention using retrospective data design with data from the VA Corporate Data Warehouse and HBPC Masterfile between October 2019 and December 2024. Eleven HBPC programs with historically low (< 50%) LST documentation rates participated in a phased intervention consisting of a 6‐month pre‐implementation phase, a 15‐month implementation phase, and a 12‐month sustainability phase. The intervention combined monthly audit and feedback reports with site‐specific implementation facilitation. We used a difference‐in‐differences (DID) analysis to compare changes in monthly site‐level LST documentation rates at intervention sites (Cohorts 1–3) versus non‐intervention sites (Cohort 4). The primary site‐level outcome was the percentage of Veterans with a completed LST template. Results: The analysis included a total of 140 VA sites, with 11 intervention sites across six VA regions. Intervention sites demonstrated a significant and sustained increase in LST documentation during implementation. The overall average treatment effect was 0.21 (95% CI: 0.144–0.276), corresponding to an average increase over expected trends of 21 percentage points across all intervention cohorts. This effect was maintained throughout the 12‐month sustainability period across all cohorts. Conclusions: Pairing audit and feedback with implementation facilitation produced a substantial and durable improvement in LST documentation in HBPC settings. These findings support the use of these two complementary, data‐driven implementation strategies to achieve policy goals of goal‐concordant care for seriously ill Veterans. Summary: Key points ○This multi‐site intervention targeting VA Home Based Primary Care (HBPC) teams demonstrated a significant, sustained increase in life‐sustaining treatment preference documentation.○Improving life‐sustaining treatment preference documentation rates by an average of 21 percentage points suggests that structured implementation can effectively promote goal‐concordant care across diverse settings.○This study contributes to the implementation science literature in geriatrics and palliative care by offering evidence for audit and feedback and implementation facilitation as effective implementation strategies.Why does this paper matter? ○This manuscript contributes actionable evidence for scaling effective implementation strategies of audit and feedback and implementation facilitation to improve life‐sustaining treatment preference documentation within complex health care systems.